Analisis Pengaruh Pengeluaran Pemerintah Dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Provinsi Sumatera Utara - Harbain, Harbain; Suryaman, Restu A (Economic Development Progress, 2024)
The Poverty is inability residents to meet their basic living needs. Although the rate of the government expenditure and economic growth is highly but poverty still high too, especially in North Sumatera Province at 2012-2022 periods. The method of research is secondary data collecting from North Sumetera central bureau of statictic, Internet site, Books, Journasl and others which relevant to the research. Location of the rearsch is 33 district/ city around North Sumatera and North Sumatera Government. The result of multiple linier regression find the estimation model Y = 1,442 +1.004E-5 X1– 8.338E-10 X2 which means constant value is 1,442, the influence of the government expenditure is positive and significant a total of 1.004E-5 and the influence of the economic growth is negative and significant a total of – 8.338E-10 . That is phenomenon of this research. The goal of research is how the influence of the government expenditure and economic growth against poverty in North Sumatera Province.